Lipopolysaccharide- and tumor necrosis factor-alpha-induced changes in prolactin secretion and dopaminergic activity in the hypothalamic-pituitary axis - de Laurentiis, Andrea (2002)
Bacterial lipopolysaccharide (LPS) affects pituitary hormone secretion, including prolactin release, by inducing synthesis and release of cytokines such as tumor necrosis factor-α(TNF-α). Since prolactin is mainly under tonic inhibitory control of dopamine, we investigated the effect of LPS and TNF-α on the hypothalamic-pituitary dopaminergic system. LPS (100-250 μg/rat, i.p.) decreased serum prolactin levels after 1 or 3 h. Sulpiride, a dopaminergic antagonist, increased serum prolactin and blocked the inhibitory effect of LPS. LPS increased hypothalamic dopamine and DOPAC concentrations and the DOPAC/dopamine ratio both in mediobasal hypothalamus and the posterior pituitary. LPS also enhanced dopamine and DOPAC concentration in the anterior pituitary. LPS elevated plasma levels of epinephrine, norepinephrine and dopamine but it did not modify the concentration of epinephrine or norepinephrine in the tissues studied. The administration of TNF-α(i.c.v., 1 h, 100 ng/ rat) decreased serum prolactin but did not affect plasma catecholamine levels. TNF-α did not modify the DOPAC/ dopamine ratio in hypothalamus or posterior pituitary but increased dopamine and DOPAC concentrations in the anterior pituitary. Incubations of hypothalamic explants showed that TNF-α did not modify in vitro basal dopamine release and reduced K+-evoked dopamine release. On the contrary, incubations of posterior pituitaries showed that TNF-α significantly increased basal and K+-evoked dopamine release. These results indicate that LPS and TNF-α increase dopamine turnover in the hypothalamic-pituitary axis. This increase in dopaminergic activity could mediate the inhibitory effect of LPS and TNF-α on prolactin release. Furthermore, the increase in dopaminergic activity elicited by LPS could be mediated by an increase in hypothalamic TNF-α during endotoxemia.